Spectral-domain OCT peripapillary retinal nerve fibre layer thickness measurements in patients with stargardt disease. Issue 5 (8th October 2010) - Genead, Mohamed A; Fishman, Gerald A; Anastasakis, Anastasios
Abstract : Aims: To evaluate the presence of peripapillary retinal nerve fibre layer (RNFL) defects in patients with Stargardt disease by using spectral-domain optical coherence tomography (SD-OCT). Methods: Fifty-two eyes of 27 patients with Stargardt disease underwent peripapillary RNFL thickness measurements using SD-OCT. Results: Twenty-seven patients with Stargardt disease were enrolled. Their mean (±SD) age was 38.3 (14.7) years. Fourteen patients (51.9%) showed a thinning of the peripapillary RNFL in one or more quadrants in at least one eye, and four patients (14.8%) in both eyes. Five patients (18.5%) showed a thickening of the peripapillary RNFL in at least one eye, and four patients (14.8%) in both eyes. Conclusion: This study demonstrated the presence of defects in the peripapillary RNFL thickness in patients with Stargardt disease by using SD-OCT. It would be clinically prudent that Stargardt patients considered for various treatment options be considered for RNFL thickness measurements.